Peran Budaya Pembelajaran dan Knowledge Management Terhadap Kinerja Perusahaan: Studi Kasus PT XYZ - Purnama, Mirawati; Budihardjo, Andreas (Universitas Prasetiya Mulya, 2008)
Nowadays, food industries face a lot of challenges and problems at the sametime, as business competition is very tough. People’s consumption life stylechanges and raw food material becomes scarce; therefore, PT XYZ, whichis a family business company, has to struggle to survive and grow. In fact,innovation becomes one of the most important factors that leads companiesto win the competition. PT XYZ, therefore, has to keep on innovating itsproduction process and products. Being innovative means that PT XYZ hasto apply learning culture as it encourages knowledge management (KM).In other words, the learning culture will support the KM activities, whicheventually will result in high corporate performance. This article discussesto which extent PT XYZ has adopted learning culture reflected on the sevendimensions of Learning Organization. A quantitative analysis was usedto identify current learning culture, and a qualitative approach was usedto explain the role of knowledge management in the learning culture.In addition to it, activities which are related to innovation, knowledgemanagement and corporate performance are described.